Interview: The City of Skopje through Cross-generational Lens - Meri Batakoja (My University, 2018)
The interview is conducted as separate conversations with four architects, with an aim to reveal their experience, thoughts and considerations about the "captured public space" of the City of Skopje. The interview unfolds individual reconstructions of the context, by personal recollections and personal views of the interlocutors; it refers on the culture that captures or frees space; the inter-relations between public space citizenship and the sensitive topics of the city's history and memory; the overlaps and disconnections between architectural profession, architectural education and state authorities...and other restrictions that prevent us from looking at the public space as free from interest and completely devoted to the values of our daily city life.
Keywords: interview, public space, free space, freeingspace, Radovan Ragjenovikj, Rancho Hristov, Martin Guleski, Vlatko P. Korobar, Skopje